Cybersecurity Practices and Supply Chain Performance: The Case of Jordanian Banks - Saleh Fahed Al-Khatib; Yara Yousef Ibrahim; Mohammad Alnadi (Administrative Sciences)
This study explores the impact of cybersecurity practices on supply chain performance in the Jordanian banking sector. A survey was used to obtain data from managers and customers. Data from 40 managers’ and 250 digital banking customers’ surveys were collected, of which 220 were valid to be analyzed using IBM SPSS V26 and PLS-SEM V4; 30 responses were excluded due to invalidity issues such as zero standard deviation and outliers identified using Cook’s distance. This study empirically demonstrates the significant positive impact of cybersecurity practices on Jordanian banking supply chain performance. Specifically, the confidentiality, integrity, and availability dimensions strongly correlate with the banks’ supply chain performance. The results indicate that managers have a high degree of cybersecurity awareness and implementation, emphasizing the significance of regular cybersecurity practice training and discussions. Customers desired improved communication and explanation on cybersecurity issues from their banks despite being generally satisfied with cybersecurity. This study’s significant contribution lies in identifying the actual levels of cybersecurity practices and supply chain performance in the Jordanian banking sector and their interaction from both managers’ and customers’ perspectives. Future investigations into the long-term impacts of cybersecurity investments and the comparative examination of cybersecurity methods across other sectors or locations would benefit greatly from this research’s insightful findings. Practically, the results highlight the value of investing in cutting-edge cybersecurity measures, training staff, and effectively explaining procedures and protocols to clients. All of these measures together improve efficiency, trust, and collaboration throughout the banking supply chain.